Digital Transformation in the Fashion Industry: Factors Influencing the Level of Professionalism - Fadhilah; Suhairi, Laili; Hamid, Yuli Heirina (MultiTech Publisher, 2024)
This study aims to identify the factors influencing the level of professionalism in the fashion industry in Banda Aceh during the digital era. Conducted in June 2024, the research used questionnaires distributed to business owners and employees in fashion stores, tailors, and related shops. Adopting a descriptive qualitative analysis approach, the study highlights the adoption of digital technology, digital readiness, digital marketing strategies, and entrepreneurial orientation as key factors influencing professionalism in the fashion industry. The findings are expected to provide insights for the industry to enhance adaptation to digital changes, address challenges, and capitalize on available opportunities.